Model of Corporate Value Improvement Through Investment Opportunity in Manufacturing Company Sector - Faozi*, Imam; Ghoniyah*, Nunung (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2019)
This study aims to analyze the significance of the direct and indirect effect ofinstitutional ownership (INST), profitability (ROI), funding policy (DER), anddividend policy (Tobin?s Q) through investment opportunity (MV/BVE). Theresearch data used 21 samples of manufacturing companies listed on theIndonesia Stock Exchange (IDX) during the 2012-2016 period. Data analysisused path analysis with the help of EViews 9 and Sobel test to know the effect ofinvestment opportunity as an intervening variable. The interpretation findingsof the first line analysis model show that Profitability directly affects positivelyand significantly on Corporate Value. Whereas, based on second-line analysismodel, Funding Policy and Dividend Policy indirectly have significant effectson Corporate Value through Investment Opportunity variable. Simultaneously,all independent variables affect 97.45% of Investment Opportunities andamounted to 97.97% of Corporate Value through Investment Opportunities.Keywords:Corporate value, institutional ownership, profitability, funding policy, dividend policy, investment opportunity.*Department of Management, Faculty of Economics, Universitas Islam Sultan Agung (UNISSULA), Jl. Kaligawe Raya Street Km.4, Semarang, 50112,PO Box 1054/SM, Indonesia. https://doi.org/10.21632/irjbs.12.2.185-196